2010
DOI: 10.1159/000314164
|View full text |Cite
|
Sign up to set email alerts
|

G-Protein-Coupled Receptor 35 Is a Target of the Asthma Drugs Cromolyn Disodium and Nedocromil Sodium

Abstract: We report that the asthma drugs cromolyn disodium and nedocromil sodium are potent G-protein-coupled receptor 35 (GPR35) agonists. We utilized calcium flux and inositol phosphate accumulation assays to examine the pharmacology of these asthma drugs on the human, mouse and rat GPR35. The compounds were more potent on the human GPR35 than on mouse and rat receptors. In contrast, zaprinast, a known GPR35 agonist, was more potent on mouse and rat GPR35 than the human ortholog. We show by quantitative PCR that GPR3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
136
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(140 citation statements)
references
References 27 publications
2
136
0
2
Order By: Relevance
“…Previous studies showed that the antiasthma and antiallergic agents cromolyn disodium (Jenkins et al, 2010;Yang et al, 2010) and nedocromil sodium (Yang et al, 2010) are modestly potent agonists of GPR35. This was confirmed in Mast Cell Stabilizers and GPR35 a PathHunter human GPR35a-b-arrestin-2 interaction and complementation assay (Table 1), with nedocromil sodium (EC 50 5 0.97 6 0.09 mM) being approximately 3-fold more potent than cromolyn disodium (EC 50 5 2.98 6 1.27 mM).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that the antiasthma and antiallergic agents cromolyn disodium (Jenkins et al, 2010;Yang et al, 2010) and nedocromil sodium (Yang et al, 2010) are modestly potent agonists of GPR35. This was confirmed in Mast Cell Stabilizers and GPR35 a PathHunter human GPR35a-b-arrestin-2 interaction and complementation assay (Table 1), with nedocromil sodium (EC 50 5 0.97 6 0.09 mM) being approximately 3-fold more potent than cromolyn disodium (EC 50 5 2.98 6 1.27 mM).…”
Section: Resultsmentioning
confidence: 99%
“…This was confirmed in Mast Cell Stabilizers and GPR35 a PathHunter human GPR35a-b-arrestin-2 interaction and complementation assay (Table 1), with nedocromil sodium (EC 50 5 0.97 6 0.09 mM) being approximately 3-fold more potent than cromolyn disodium (EC 50 5 2.98 6 1.27 mM). Because GPR35 is expressed by human mast cells and levels are reportedly upregulated by exposure to the allergic stimulus IgE (Yang et al, 2010), we set out to investigate whether other antiallergic ligands and mast cell stabilizers might also act as agonists at GPR35 and, if so, potentially provide a common mode of action. Bufrolin (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antiasthma medicine and histamine sensitizer cromolyn disodium ( Fig. 1) (Jenkins et al, 2010;Yang et al, 2010) also acted as an agonist with efficacy equal to that of zaprinast at all three species orthologs. In this case ligand potency was lower, but was relatively similar between the human and rat orthologs with pEC 50 ϭ 4.78 Ϯ 0.10 (mean Ϯ S.E.M.…”
Section: Pamoate Is a Highly Selective But Partial Agonist Formentioning
confidence: 99%